The Effect of Elsa Speak for Increasing Speaking Ability in Junior High School at SMPN 4 Bengkulu - Mareisca Ilham; Ferri Susanto; Anita Anita (Ikatan Dai Indonesia, 2025)
This study aims to examine the effect of the ELSA Speak application on improving the speaking ability of eighth-grade students at SMPN 4 Bengkulu. The background of this research arises from students’ low speaking performance due to conventional teaching methods, limited speaking practice, and insufficient integration of technology in English instruction. The study employed a quasi-experimental method using a Non-Equivalent Control Group Design, involving two classes and a total of 68 students. The speaking test instrument assessed fluency, accuracy, pronunciation, and linguistic complexity. The findings revealed a significant improvement in the experimental class using ELSA Speak, with the average score increasing from 55.88 to 68.76. Meanwhile, the control class increased from 55.00 to 62.41. The independent sample t-test obtained a significance value of 0.022 < 0.05, confirming that ELSA Speak had a significant effect on student speaking ability. Therefore, ELSA Speak is proven to be an effective technology-based learning tool for enhancing students’ speaking skills at the junior high school level.